In Seeking of Legal Protection : Local Workers in Wetland Area of Tanah Bumbu District. - Abdul Halim Barkatullah; Ifrani; Lena Hanifah (Journal of Wetlands Environmental Management, 2016)
Local worker is a crucial issue that challenges the capability of local government in protecting the community, particularly in developing district which the skills and education is poorly distributed. Globalization enforced penetration of non-local skilled workers (such as immigrants), and instead of having the technology transferred, it also threatened the unskilled local workers. Legal protection for local workers is highly needed to ensure the application of Pancasila’s social justice and to avoid massive unemployment in such area. The research situated in Tanah Bumbu District, South Borneo, Indonesia, which famed with its mining industry that attracted many workers, not only regionally, but also globally, to test their luck. However, not all locals taste the sweetness of the mining industry. Instead of providing new job vacancies for local workers, company tends to hire non-local workers due to their competency and ability to meet the company’s requirement. This has to be a concern of the local government, therefore this paper aimed to find the best solution in the form of local regulation to protect and empower local workers in Tanah Bumbu District, South Borneo, Indonesia.